Loyal Unto Death : Trust and Terror in Revolutionary Macedonia - Brown, Keith, 1964- (Book collections on Project MUSE., 2013)
The underground Macedonian Revolutionary Organization recruited and mobilized over 20,000 supporters to take up arms against the Ottoman Empire between 1893 and 1903. Challenging conventional wisdom about the role of ethnic and national identity in Balkan history, Keith Brown focuses on social and cultural mechanisms of loyalty to describe the circuits of trust and terror-webs of secret communications and bonds of solidarity-that linked migrant workers, remote villagers, and their leaders in common cause. Loyalties were covertly created and maintained through acts of oath-taking, record-kee.